DAMPAK POSITIF DAN NEGATIF PERKEMBANGAN TEKNOLOGI ABAD 21 - Fricticarani, Ade; Fitria, Ainatul; Rahmawati, Indah; Safitri, Ira; Janah, Sri Wardatul (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
The 21st century development of information technology development is very fast and automated in which many jobs and character Routine work, both production machines and computers. Like to be known in the 21st century. Society has completely changed and the world of Education In the 21st century there is only one race of decades, but in the world of education you have felt the changes, and even fundamental changes at the level of philosophy, direction and goals. Technology is used sparingly and used properly, because it already knows its impact, increases knowledge, and increases student motivation to learn technology. The suggestions made are need follow-up in the form of evaluation, as well as increase the creativity of students in using technology